Spatial Analysis of Realization of Creative City Indicators in Urban Neighborhoods (Case Study: Zanjan City) - Hossien TahmasebiMogaddam; isa piri; zahra Rasolzadeh; Mahnaz Vaezlivari (تحقیقات کاربردی علوم جغرافیایی)
The endogenous growth pattern reflects the importance of the quality of human capital and even the social system and governance in which culture is considered as the source of ideas for economic sectors. A review of the policies and priorities for the development of the new economy highlights the importance of creative city indicators in managing the challenges and cultural and economic diversity of current cities. The research method in this study is descriptive-analytical and it is applied in terms of purpose. . The method of data collection is mainly library and documentary by means of catch-up, housing statistical blocks of 2016 and detailed plan map of 2015. Combined methods of  the factor analysis and spatial statistics in GIS are used for analysis. Most of Zanjan's neighborhoods lacked creative class attraction indices and spatial distribution of Zanjan's central and northern creative city indices was relatively favorable. Zanjan's neighborhood development policies have less attention to the interests and priorities of the creative class, and urban spaces other than the central and northern neighborhoods are not conducive to social interaction and creativity of residents, and urban residents, especially urban east and west, have become passive recipients of urban services and facilities.